FRI0167 Effect of Infliximab and Paricalcitol on Inflammation and Mineralization/Calcification of Mesenchymal Stem Cells during Osteogenic Differentiation. (10th June 2014) - Ruiz-Limon, P.; Cerdo-Raez, T.; Herencia, C.; Muñoz-Castañeda, J.; Jimenez-Gomez, Y.; Perez-Sanchez, C.; Carretero, R.; Barbarroja, N.; Lopez-Pedrera, C.; Escudero, A.; Collantes, E.
Abstract : Background: Spondyloarthropathies are a group of chronic inflammatory diseases characterized by progressive new bone formation leading to ankylosis and functional disability. TNF antagonists are effective and safe long-term treatments in patients with spondyloarthropathies with inadequate response to NSAIDS. However, the beneficial effects of anti-TNF therapies on radiological evolution of these patients have not yet been demonstrated. Paricalcitol, a synthetic form of vitamin D, diminishes the calcification. It has been shown that plasma levels of vitamin D are reduced in patients with ankylosing spondylitis (AS) which inversely correlated with their inflammatory status Objectives: To evaluate the effect of anti-TNF, paricalcitol and the combined treatment of both compounds on inflammatory and osteogenic differentiation processes of mesenchymal stem cells Methods: Mesenchymal stem cells were obtained from bone marrow of healthy donors and differentiated into osteoblasts using dexamethasone, b-glycerophosphate and ascorbic acid. Alkaline phosphatase (AP) activity and alizarin red staining were used as differentiation and mineralization markers at 7, 14 and 21 days. After 14 days of differentiation, infliximab (100μM), paricalcitol (3x10 –8 M and 3x10 –10 M) and the combined treatments of both compounds were added to cell cultures and maintained during 7 days. Markers of new bone formation (BMP-2, osteocalcin, Runx2, osterix, AP), inflammation (IL-1b, IL-6, IL-8, IL-23, MCP-1, TGFb y VEGF) and intracellular signaling molecules (STAT3) were determined by RT-PCR and Western-blot. Wnt/b-catenin pathway regulation was evaluated by Western-blot of phosphorylated and total protein and RT-PCR of Wnt and Dkk1 Results: An increase in AP activity and alizarin red staining after 21 days of treatment was observed. The gene expression of several osteogenic genes (i.e. BMP-2 and Runx2) was significantly elevated. Osteogenic differentiation further promoted an increase in the gene expression of cytokines/chemokines (i.e. IL-1b, IL-6, IL-8, IL-23, MCP-1, TGF1b) and regulatory molecules (STAT3). Paricalcitol and anti-TNF treatment produced a significant reduction of inflammatory profile present in osteoblasts. Yet, none treatment modulated the osteogenic process. A reduction in STAT3 activity by effect of anti-TNF and paricalcitol was observed, which was parallel to the decreased gene expression of inflammatory cytokines. None treatment promoted variations in b-catenin expression, suggesting that this molecule is not involved in the bone formation process. The combined treatment did not alter the gene expression profiles in relation to each treatment given alone Conclusions: 1) Paricalcitol promotes an inhibition of inflammatory profile in osteoblast cells similar to anti-TNF treatment. 2) After osteoblast differentiation, this process is not reverted by anti-TNF or paricalcitol treatment. Thus, paricalcitol might prevent the vitamin D deficiency demonstrated in patients with AS, thereby contributing to the reduction of the inflammatory status and the prevention of osteoporosis, a concominant symptom of bone damage in patients with AS Acknowledgements: Supported by JA PI-0314-2012 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5076